Rapid screening of 70 colorants in dyeable foods by using ultra-high-performance liquid chromatography–hybrid quadrupole–Orbitrap mass spectrometry with customized accurate-mass database and mass spectral library. (15th September 2021) - Wu, Wenlin; Liu, Shiyao; Guo, Tianrong; Han, Xiying; Xia, Bing; Wan, Yuping; Han, Quanbin; Zhou, Yan
Highlights: UHPLC-Q/Orbitrap HRMS was used for rapid screening of 70 colorants in seven types of dyeable foods. Customized accurate-mass database and mass spectral library for 70 colorants were established. UAE and dSPE were employed in sample pretreatment. The developed approach was applied for the analysis of 150 real samples. Abstract: A rapid screening method of 70 colorants for regulatory control in dyeable foods was established using ultra-high-performance liquid chromatography–hybrid quadrupole–Orbitrap mass spectrometry (UHPLC-Q/Orbitrap MS) with customized accurate-mass database and mass spectral library. A rapid, high-throughput, and simple sample pretreatment condition with low reagent consumption and high recovery was developed on the basis of ultrasound-assisted extraction and dispersion solid-phase extraction. Rapid screening was conducted by comparing the experimentally measured exact mass of the parent and fragment ions, the isotope pattern, and the retention time with the accurate-mass database and by matching the acquired MS/MS spectra against the mass spectral library. The performance of the method was evaluated in terms of linearity, limits of detection, limits of quantitation, recovery, repeatability, reproducibility, and matrix effect. The proposed method was applied for simultaneous analysis of 70 colorants in seven kinds of dyeable foods, and it exhibited great potential for broad, sensitive, and reliable.